Evaluation of digital competencies development of an instrument for vocational teacher training - Sänger, Niklas [Verfasser] (My University, 2024)
"Approaches to modeling and evaluating teachers’ digital competencies are often based on the TPACK model. However, in-depth analyses of the conceptualization of the model show that the specificities of the so-called dual subject matter of vocational education are not sufficiently represented. This article provides insights into the development and testing of an instrument for teachers’ self-assessment of digital competencies in vocational education. The instrument is based on the structure of TPACK but is adapted in various ways to reflect the specificities of vocational education. The aim of this article is to transfer a conceptual extension of the TPACK model into an initial instrument and to analyze it as part of an initial exploration." (author's abstract; BIBB-Doku)
Keywords: P 3.2.3 Lehrer; 370; Berufsschullehrer; Lehrerbildung; Digitalkompetenz; Kompetenzmodell; Selbsteinschätzung